Radiological improvement by tocilizumab in polyarticular juvenile idiopathic arthritis. Issue 2 (April 2015) - Tozawa, Yusuke; Fujita, Shouji; Abe, Shuji; Kitamura, Koichi; Kobayashi, Ichiro
Abstract Recent advances in biologic therapy have enabled reduction of the progression of destructive arthritis in rheumatoid arthritis. Once destroyed, however, the affected bones and cartilage are not fully repaired. We describe the case of an 8‐year‐old girl with anti‐citrullinated peptide antibody (ACPA)‐positive polyarticular juvenile idiopathic arthritis (p‐JIA). Destructive arthritis progressed during combination therapy with infliximab, methotrexate, mizoribine and prednisolone. Clinical remission was achieved, however, after switching the biologic agent to tocilizumab, a humanized monoclonal antibody to interleukin‐6 receptor. Both bone erosion and bone marrow edema on magnetic resonance imaging were repaired in association with restoration of joint spaces. Furthermore, there was no relapse of arthritis on weekly methotrexate alone for 2 years after discontinuation of the tocilizumab. Tocilizumab led to radiological repair of both bone and cartilage destruction and long‐term biologics‐free remission in a patient with ACPA‐positive p‐JIA, and should be considered for tumor necrosis factor inhibitor‐resistant cases.